KOMUNIKASI POLITIK PEREMPUAN DI KEDIRI - Citra Orwela (Jurnal Anifa: Studi Gender dan Anak, 2023)
The limited number of women involved in political activities, both local and national, is an exciting problem to be examined. Until now, research on women politicians and leadership has not been explored. Starting from these problems, the author wants to go deep into deep research on "Women's Political Communication in Kediri". This study took two informants of female politicians in Kediri. This research is a qualitative type which was conducted by the phenomenological paradigm with an interpretive approach. The results of this study found the importance of communication abilities and skills in the political field.